PERBEDAAN HASIL BELAJAR IPA SISWA KELAS VIII SMP NEGERI 11 YOGYAKARTA ANTARA METODE INQUIRY ROLE APPROACH (IRA) DENGAN METODE DEMONSTRASI - Siti Zainap; Hidayati Hidayati; Astuti Wijayanti (N A T U R A L: Jurnal Ilmiah Pendidikan IPA, 2015)
This study aims to know the tendency of science learning outcomes in 8th grade students of SMP Negeri 11 Yogyakarta students in the academic year of 2014/2015 with used the Inquiry Role Approach (IRA) method and demonstration method. Comparatively to determine differences in science learning outcomes in 8th grade students of SMP Negeri 11 Yogyakarta students in the academic year of 2014/2015 between Inquiry Role Approach (IRA) method and demonstration method. The results showed that the tendency of the science learning outcomes of students using method Inquiry Role Approach (IRA) is very high while the tendency of learning outcomes of students using demonstration method is high. The analysis showed that there differences science learning outcomes in 8th grade students of SMP Negeri 11 Yogyakarta students in the academic year of 2014/2015 between Inquiry Role Approach (IRA) method with demonstration method.